Adolescent Behavior on Social Networks in the Context of Safety - Papoyan, Varduhi; Galstyan, Alina; Muradyan, Elena; Poghosyan, Rima; Manukyan, Mariam (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
This article delves into the impact of social networks on adolescents concerning their well-being and safety. It discusses the ambivalence of social media’s influence on adolescents, exploring their communication patterns, interactions, and its effect on the overall educational process. Additionally, it examines how social networks affect adolescents, considering the nuances of the educational institutions they attend. Special attention is given to the issue of cyberbullying. A questionnaire was developed to identify destructive behaviors among social network users that most concern adolescents regarding their safety. The study aims to understand adolescent behavior and attitudes toward social networks concerning their well-being and safety. Variations in adolescent behavior on social networks were observed based on the type of school they attend. The study adapted and employed scales to distinguish between adolescents’ behavior on social networks outside of school and within school premises. Both positive and negative effects of social networks on adolescent behavior were identified through the study. Tables presenting correlation analyses between indicators of adolescent behavior on social networks at school and outside school, along with structured interview results, are provided. The article highlights the content aspects of teenagers’ behavior on the internet and social networks, emphasizing the relevance of cyberbullying among teenagers. It concludes by emphasizing the necessity of cyber awareness among adolescents to ensure psychological safety and security in the virtual realm.